Promoting Self-Control through Reflective and Participatory Emotional Training: A Macro-Level Intervention for Adolescent Girls in An Orphanage - Fitri, Rindifa Amilatul; Aulia, Ranisya Wilda; Karyani, Usmi (Universitas Muhammadiyah Surakarta, 2025)
This study aimed to enhance self-control among children at Aisyiyah Girls Orphanage in Grogol, Sukoharjo using modul intervention